Peripheral CD56+CD16+ NK Cell Populations in the Early Follicular Phase Are Associated With Successful Clinical Outcomes of Intravenous Immunoglobulin Treatment in Women With Repeated Implantation Failure - Ho, Yao-Kai; Chen, Hsiu-Hui; Huang, Chun-Chia; Lee, Chun-I; Lin, Pin-Yao; Lee, Maw-Sheng; Lee, Tsung-Hsien (Frontiers in Endocrinology, 2020)
The percentage of peripheral CD56+CD16+ NK cells in the early follicular phase on days 2–3 of the menstrual cycle in repeated implantation failure (RIF) patients was used to evaluate the impact of intravenous immunoglobulin (IVIG) on ART cycles. A total 283 patients with RIF consisting of at least 3 ART failures and at least 2 high quality embryo transfers were recruited. A logistic regression analysis for the peripheral immunological profile was completed to predict implantation success and compare the implantation and pregnancy rates between groups with ≤10.6 and >10.6% of CD56+CD16+ NK cells in the early follicular phase. The logistic regression and receiving operating curve analyses showed that patients with ≤ 10.6% of peripheral CD56+CD16+ NK cells in the early follicular phase showed a lower pregnancy rate within the RIF group without IVIG. Patients with peripheral CD56+CD16+ NK cells ≤ 10.6% and without IVIG treatment showed significantly lower implantation and pregnancy rates (12.3 and 30.3%, respectively) when compared with the CD56+CD16+ NK cells >10.6% group (24.9 and 48.0%, respectively, p < 0.05). Furthermore, the patients with CD56+CD16+ NK cells ≤ 10.6% given IVIG starting before ET had significantly higher implantation, pregnancy, and live birth rates (27.5, 57.4, and 45.6%, respectively) when compared with the non-IVIG group (12.3, 30.3, and 22.7%, respectively, p < 0.05). Our results showed that a low percentage of peripheral CD56+CD16+ NK cells (≤10.6%) in the early follicular phase is a potential indicator of reduced pregnancy and implantation success rates in RIF patients, and IVIG treatment will likely benefit this patient subgroup.